The preparation and characterization of gold-conjugated polyphenol nanoparticles as a novel delivery system - Hsieh, Dar-Shih (Dove Medical Press, 2012)
Nanogold particles are commonly used in nanomedicine. We generated physical nanogold (pNG) conjugated with different ratios of epigallocatechin-3-gallate (EGCG) and evaluated its physicochemical properties, antioxidant activity, and cytotoxicity in vitro as well as anticancer activity in vivo. Results showed that the EGCG-pNG conjugates were successfully prepared at ratios between 23:1 and 23:5, with the percentage of EGCG content increasing with the EGCG:pNG ratio from 23:1 (2.0% ± 0.02%) to 23:5 (28% ± 0.3%). EGCG-pNG particles at ratios of 23:1 and 23:5 demonstrated significantly decreased size from 500 to 20 nm and decreasing zeta potentials of 21 mV to −22 mV, respectively. At a ratio of 23:2.5, the EGCG-pNG particles (27% EGCG, 50 nm in size, zeta potential of −8 mV) showed longer EGCG activity half-life (110 days vs 5 hours), controlled release (2 hours vs 30 minutes), and higher antioxidant activity (four times), as well as inhibition of tumor cell growth, than controls. The present study indicated that EGCG-pNG possesses promising therapeutic potential, based on its strong free-radical scavenging and anticancer activities.